Efforts To Improve Understanding Of Plans And Maps For Class Iii Primary Students - Gunawan, Bambang Endra (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
He purpose of the study was to determine the effectiveness, advantages and disadvantages of applying the Inquiri method and exercises in grade III elementary school social studies learning in understanding floor plans and maps. The subjects in this study were grade III students. Research techniques are Classroom Action Research (PTK), data collection techniques using observations, written tests, and data analysis techniques using comparative descriptive analysis, namely comparing the results of observation tests since the initial conditions, cycle I, and cycle II, as well as reflection on the results of reflection. Resulting in an average value increase of 27%, 63.5 in cycle I, to 87 in cycle II. With the Inquiri method and exercises to make social studies learning more effective, increase the percentage of completeness from cycle I to cycle II reaches 100%, and can increase the understanding of grade III social studies maple students of SD Negeri 1 Beteng.